Bases para una nueva interpretación sobre las mujeres en la Prehistoria - Masvidal Fernández, Cristina (Complutum, 2007)
The feminine figurines found in Palaeolithic and Neolithic European sites have been the base for multiple propositions about women’s condition in prehistory. In this essay I want to go further in this issue analyzing this group of figurines from a feminine point of view. I pay special attention to the domestic context and to the spatial relationships of figurines with the others archaeological remains that will provide new arguments about prehistoric women and their social relations. I propose two clearly differentiated models - the Palaeolithic one, represented by the figurines of Gravetian and Magdalenian cultural periods, and another one for the Neolithic groups in Greece and the Balkans - which stand against the uniformitarian argument of interpreting the figurines as representations of a goddess.